Peran Perempuan Dalam Pengembangan Lembaga Keuangan Mikro Syariah Di Kabupaten Tanah Datar - Muhammad Rizal (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2014)
Islamic financial institutions have a very important position as an institution of sharia-based Islamic economics in the national development process and can keep people from usury economic system. The existence of Islamic financial institutions, both banks and non-bank affects the religious life of Muslims as a whole, regardless of sex male or female. Especially on non-bank financial institutions in the form of Islamic financial services cooperative that is in the villages will be showing the involvement of women in policy making and operation of the financial institution. In addition, with the position of women as housewives who take an important role in regulating the domestic financial system. Islamic microfinance institutions in Tanah Datar District pioneering majority are women so that they directly act as manager thus everything that is related about the policy and decision-making for the development of financial institutions and Mikros dominant operation is done by women. Thus women in Islamic microfinance institutions in Tanah Datar has major role in determining the development of the Islamic microfinance institutions.